Adoption of sustainable intensification in dual-purpose millet – leguminous crops – livestock systems in Senegal - Min, Doohong (Kansas State University, 2016)
Dr. Doohong Min, Senegal subaward leader for the Feed the Future Innovation Lab for Collaborative Research on Sustainable Intensification (SIIL), introduces his project to the SIIL community. Filmed in January 2016.